Improving Learning Management System Performance: A Comprehensive Approach to Engagement, Trust, and Adaptive Learning - Latifa Abdullah Almusfar (IEEE Access)
This paper examines the critical factors influencing the performance of Learning Management Systems (LMS), emphasizing user satisfaction and loyalty. Employing a quantitative approach, structural equation modeling (SEM) was used to analyze survey data from 266 university students actively utilizing LMS platforms. Findings reveal that system quality significantly impacts user satisfaction, emphasizing reliability and usability. Adaptive learning enhances satisfaction and engagement by tailoring educational content to individual needs. Trust, particularly regarding data security and system reliability, further contributes to satisfaction, underscoring the necessity of robust and transparent security measures. Although information quality positively affects user satisfaction, it is less impactful than system-related factors. Service quality, while exerting a smaller influence, highlights the importance of responsive technical support for overall functionality. Additionally, user satisfaction strongly predicts user loyalty, indicating that satisfied users are more likely to continue using and recommending LMS platforms. The study provides actionable insights for developers and educators, advocating for enhanced system performance, adaptive learning tools, and trust-building measures to foster satisfaction and loyalty.